Avoiding the ask on social media: investigating how process-related factors influence SNS donation avoidance. Issue 3 (1st December 2020) - Li, Xiaodong; Zhang, Chen; Chen, Juan; Zhang, Shengliang
Abstract : Purpose: The domain of monetary donation is evolving with the combination of professional donation platforms and social network sites (SNSs) in the agency process, potentially enhancing information communication and facilitating money transfers between donors and recipients. However, SNS donation avoidance hinders the leveraging of significant economic and social values. To address the limited understanding of the phenomenon of SNS donation avoidance, this study aims to investigate the influencing factors of people's avoidance behavior in the agency process of SNS donation. Design/methodology/approach: A model was devised containing four process-related factors (requests overload, process ambiguity, channel security concerns and perceived distributive injustice) as antecedents of SNS donation avoidance, with probable mediating paths of negative emotions, altruistic outcome expectation and egoistic outcome expectation. Data were collected through a survey of 398 users of WeChat Moment in China. Structural equation modeling was used to analyze the proposed model. Findings: All four process-related factors have positive associations with SNS donation avoidance. Requests overload, channel security concerns and perceived distributive injustice all positively influence people's expectation of negative emotions and lead, in turn, to their SNS donation avoidance. Perceived distributive injustice also leads to SNS donation avoidance via negatively influencing people's expectations of both altruistic and egoistic outcomes. Originality/value: Theoretically, this empirical study synthetically associates process-related factors to donation avoidance through the paths of emotional responses and rational outcome expectations. Practically, it emphasizes key factors to consider in the process management of SNS donation.